Assessment of Bioflocculant Production by Bacillus sp. Gilbert, a Marine Bacterium Isolated from the Bottom Sediment of Algoa Bay - Okoh I. Anthony; Mabinya V. Leonard; Cosa Sekelwa; Piyo Nontembiso (Marine Drugs, 2011)
The bioflocculant-producing potentials of a marine bacteria isolated from the bottom sediment of Algoa Bay was investigated using standard methods. The 16S rDNA sequence analysis revealed 98% similarity to that of Bacillus sp. HXG-C1 and the nucleotide sequence was deposited in GenBank as Bacillus sp. Gilbert with accession number HQ537128. Bioflocculant was optimally produced when sucrose (72% flocculating activity) and ammonium chloride (91% flocculating activity) were used as sole sources of carbon and nitrogen, respectively; an initial pH 6.2 of the production medium; and Mg2+ as cation. Chemical analysis of the purified bioflocculant revealed the compound to be a polysaccharide.